Conjugate Tooth Profile Solving and Movement Interference Inspection of Harmonic Type Gear Pump - Liu Ziyao; Zhu Hailin; Li Youwu (Jixie chuandong)
Aiming at the problems that the flexspline of harmonic type gear pump could easily lead to tooth interference during the process of gear meshing,according to envelope theory,the mathematical model of tooth profile of flexible gear is established when conjugate involute profile of rigid gear is given. The numerical solution of tooth profile of flexible gear is got by using MATLAB,and the motion simulation of harmonic gear pump is simulated. The results show that a problem of interference is solved by adjusting clearance of radial and tooth.